Guanxinkang Decoction Attenuates the Inflammation in Atherosclerosis by Regulating Efferocytosis and MAPKs Signaling Pathway in LDLR−/− Mice and RAW264.7 Cells - Yifan Zhang; Jie Ding; Yiru Wang; Xiaoteng Feng; Min Du; Ping Liu (Frontiers Media S.A., 2021)
Guanxinkang decoction (GXK), a traditional Chinese medicinal drug, is used to treat cardiovascular disease. The aim of the study was to investigate the effects of GXK on inflammation in LDLR−/− mice and RAW264.7 cells. Fed with high fat diet for 12 weeks, the mice were randomly divided into six groups, then administered with oral 0.9% saline or GXK (7.24, 14.48, and 28.96 g/kg) or Atorvastatin (1.3 mg/kg) for 12 weeks. RAW 264.7 cells were induced with ox-LDL or ox-LDL plus different concentrations of GXK (1.25, 2.5, and 5 μg/ml), or ox-LDL plus GXK plus MAPKs activators. Serum lipid profiles and inflammatory cytokines were detected by ELISA, gene expression by RT-qPCR, plaque sizes by Oil Red O, α-SMA, caspase 3, NF-κB p65 and TNF-α production by immunofluorescence staining, and protein expression by Western Blot. The phagocytic ability of cells was determined by neutral red uptake assay. Efferocytosis-related proteins (AML, MERTK, TYRO3 and MFGE8) and MAPKs pathways were detected by Western Blot. Compared to mice fed with high fat diet, the mice with GXK showed lower cholesterol, triglyceride, low-density lipoprotein cholesterol, IL-1β, IL-6, and TNF-α, smaller plaque sizes, higher α-SMA, and lower caspase 3 and NF-κB p65 in aortic roots. RAW264.7 cells treated with ox-LDL plus GXK had lower IL-1β, IL-6, and TNF-α. GXK also increased the phagocytic ability of cells. High levels of AML, MERTK, TYRO3 and MFGE8, and decreased levels of iNOS, VCAM-1, LOX-1 and MCP-1, and phosphorylation of ERK1/2, JNK, p38, and NF-κB were detected in GXK-treated group. MAPKs activators reversed the effects of GXK in repressing inflammation and promoting phagocytosis. These results suggested that GXK could attenuate atherosclerosis and resolve inflammation via efferocytosis and MAPKs signaling pathways in LDLR−/− mice and RAW264.7 cells.